Development and Evaluation of Multilingual Education Materials to Promote Immigrant Women's Adaptation to Pregnancy - Kyung Won Kim; Sung Hee Baik; Geum Hee Jeong (Korean Society of Women Health Nursing, 2014)
PURPOSE: This study was done to develop and evaluate multilingual education materials to promote health and adaptation to pregnancy for immigrant women in Korea. METHODS: This study had three procedures: First, contents of the education materials were developed according to pregnant women's needs, literature reviews, and group discussion. Details in contents were constructed based on Roy's adaptation model; Second, validity verification and translation of education materials were accomplished; Third, evaluation of the education materials was done through a survey of immigrant women. RESULTS: The education materials were developed in six languages (Korean, English, Chinese, Vietnamese, Filipino, and Cambodian). The title is "Healthy mother, happy family: eight-step guide to a healthy pregnancy". It was composed of an eight-step guide to healthy pregnancy, self-examination check list, websites for childbirth education and information, and guidelines on education materials in a brochure. In the evaluation, the average response score for the questionnaire items was high (3.23 on a four-point Likert scale). The average score for Cambodian immigrants was the highest of all immigrant women. CONCLUSION: Multilingual education materials developed in this research will help community health nurses to manage pregnancies for immigrant women and will be useful for health education for these women.